The features of the organizational culture and its relationship to the organizational elements in the institution - BOUMAARAF, Nassima (Social Sciences Journal)
We try through this article define the general features of organizational culture and determine its importance and identify its dimension and components and various forms. We also seek to clarify the relationship between organizational culture and other organizational elements in the organization, and to clarify the nature of the reciprocal and complementary relationship between them